Handbook of research on civil society and national security in the era of cyber warfare - Hadji-Janev, Metodi, 1976-; Bogdanoski, Mitko, 1977- (Hershey, PA : Information Science Reference, 2016)
'This book addresses the problem of cyber terrorism head-on, first through a review of current literature, and then through a series of progressive proposals aimed at researchers, professionals, and policymakers'--
Includes bibliographical references (pages 495-535) and index.
Keywords: Cyberterrorism; Security, International; National security; Civil society; Cyberspace operations (Military science)